2012
DOI: 10.1111/j.1440-0960.2012.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Office based dermatological surgery and Mohs surgery: A prospective audit of surgical procedures and complications in a procedural dermatology practice

Abstract: This study supports the view that dermatological surgery, including significant procedures such as Mohs micrographic surgery, flaps and grafts, can be performed on an ambulatory basis in an office-based procedure room setting, with low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…[3][4][5][6][7] Therefore it is necessary to provide high-quality data that establishes the safety of our medical practices. Multiple prospective [8][9][10][11][12] and retrospective 13,14 studies have demonstrated the safety of MMS as performed by appropriately trained dermatologic surgeons in an outpatient setting under local anesthesia, but the number of interpolated flaps in these studies was too small to draw appropriate conclusions regarding the safety of more complicated reconstructive procedures in an ambulatory setting.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] Therefore it is necessary to provide high-quality data that establishes the safety of our medical practices. Multiple prospective [8][9][10][11][12] and retrospective 13,14 studies have demonstrated the safety of MMS as performed by appropriately trained dermatologic surgeons in an outpatient setting under local anesthesia, but the number of interpolated flaps in these studies was too small to draw appropriate conclusions regarding the safety of more complicated reconstructive procedures in an ambulatory setting.…”
mentioning
confidence: 99%
“…In recent years, more retrospective and prospective analyses have been performed, capturing a wider patient cohort and resulting in a more thorough understanding of the multiple risks of scalpel‐based cutaneous surgery (see Table 1). 7‐14 …”
Section: Complications Associated With Cutaneous Surgerymentioning
confidence: 99%
“…Reported complications of MMS include hemorrhage/hematoma, wound infection, wound dehiscence, flap/graft necrosis, and nerve injury, occurring in approximately 0.7% to 2.6% of surgeries. [15][16][17][18][19] The largest multicenter prospective cohort of 20,821 procedures using MMS noted a 0.72% adverse event rate, the most severe of which was reported as hospitalization for infectious complications in 4 patients. 17 Notably, no deaths have been reported as a complication of MMS, despite advanced age and multiple comorbidities.…”
Section: Safety In An Office-based Setting Key Pointsmentioning
confidence: 99%